Optimization of Incubation Time on Cellulase Enzyme Production Using Aspergillus niger Under Solid State Fermentation - Sukma Budi Ariyani; Asmawit Asmawit; Pramono Putro Utomo (Biopropal Industri, 2014)
Cellulase is an important enzyme for industry which can be obtained from cheap tropical agrowastes such as durian peel. West Kalimantan, in particular Pontianak city produces tons of durian peel waste during harvest season each year. This study used durian peel waste as substrates and A. niger to produce cellulase, The aim of this study is to determine the optimum incubation time in producing cellulase under solid state fermentation. Different incubation time (48, 72, 96, 120 and 144 hours) were applied for the production of cellulase. The optimum cellulase production was 120 hours of incubation, giving  protein content of 0.3960% and enzyme activity of 1,069.01 ppm, respectively.